2021
DOI: 10.1007/13836_2021_94
|View full text |Cite
|
Sign up to set email alerts
|

Population Genomics of Yams: Evolution and Domestication of Dioscorea Species

Abstract: Yam is a collective name of tuber crops belonging to the genus Dioscorea. Yam is important not only as a staple food crop but also as an integral component of society and culture of the millions of people who depend on it. However, due to its regional importance, yam has long been regarded as an “orphan crop” lacking a due global attention. Although this perception is changing with recent advances in genomics technologies, domestication processes of most yam species are still ambiguous. This is mainly due to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 94 publications
1
21
0
Order By: Relevance
“…Based on the allele variant segregation analyses, sex in D. rotundata was controlled by the female parent since more than 90% of female clones were heterozygous for sex markers while the male population was 92–100% homozygous. Using a different method (GWAS) and different plant materials, this study confirmed the female heterogametic sex determination (ZZ/ZW) system proposed for D. rotundata yam [ 7 , 11 , 17 ]. In such a system, ZW determines female sex phenotype and ZZ the male sex phenotype.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Based on the allele variant segregation analyses, sex in D. rotundata was controlled by the female parent since more than 90% of female clones were heterozygous for sex markers while the male population was 92–100% homozygous. Using a different method (GWAS) and different plant materials, this study confirmed the female heterogametic sex determination (ZZ/ZW) system proposed for D. rotundata yam [ 7 , 11 , 17 ]. In such a system, ZW determines female sex phenotype and ZZ the male sex phenotype.…”
Section: Discussionsupporting
confidence: 68%
“…Flowering in D. rotundata is characterized by a female heterogametic sex determination system (ZZ/ZW), and maleness is the default phenotype [ 7 ]. Hence, monoecy could be expressed as the failure of the W allele to feminize a subset of flowers [ 7 , 11 ]. The ZW individuals can potentially change sex over time and across locations, indicating that the Z-suppressing function can be affected by the environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was partly explained by the vegetative propagation (planting tubers) used for yam cultivation since its domestication. This clonal propagation gradually reduced the genetic diversity and led to the vulnerability to plant diseases and the difficulty of purging deleterious mutations from the germplasms [13]. Broadening the genetic base of existing yam (Dioscorea spp.)…”
Section: Introductionmentioning
confidence: 99%
“…The genus Dioscorea consists of ~600 yam species, of which eight are grown in West Africa, where D. cayenensis and D. rotundata are native and predominant species [16,17]. These two native species emerged from the domestication of wild yams, mainly, D. praehensilis, D. burkilliana, and D. abyssinica [13,18,19]. These wild yam species which are related to the cultivated species, therefore, constitute a vast reservoir of genetic resources that can be exploited to improve the white Guinea yam.…”
Section: Introductionmentioning
confidence: 99%